Bioactivities and molecular networking-based elucidation of metabolites of potent actinobacterial strains isolated from the Unkeshwar geothermal springs in India - Mehetre, Gajanan T.; Vinodh, J. S.; Burkul, Bhushan B.; Desai, D.; Santhakumari, B.; Dharne, Mahesh S.; Dastager, Syed G (RSC Advances, 2019)
The bioactive potential of Actinobacteria endemic to hot springs has rarely been investigated. This study highlights the cultivable diversity and bioactivities of Actinobacteria associated with the Unkeshwar hot springs, India. Potent strains were evaluated for their biosynthetic potentials and metabolite analysis was performed using effective dereplication molecular networking tools. A total of 86 actinobacterial strains were isolated and grouped into 21 distinct genera, based on 16S rRNA gene sequence analysis. These strains included rare members such as Micromonospora, Marmoricola, Actinomadura, Cellulomonas, Cellulosimicrobium, Janibacter, Rothia, Barrentisimonas, Dietzia and Glycomyces. In antimicrobial screening, Micromonospora sp. strain GH99 and Streptomyces sp. strain GH176 were found to be potent antimicrobial strains. The metabolic extracts of these strains exhibited strong antimicrobial activity against Staphylococcus epidermidis (NCIM 2493), Shigella flexneri (NCIM 5265), Klebsiella pneumonia (NCIM 2098), and Salmonella abony (NCIM 2257). The extracts also displayed strong anti-biofilm and anticancer activities against Pseudomonas aeruginosa (NCIM 5029), Acinetobacter junii (NCIM 5188) and breast cancer cell line MCF7, respectively. Both strains also tested positive for the presence of the PKS biosynthetic gene cluster in their genomes. To effectively delineate the secondary metabolites, the extracts were subjected to MS/MS-guided molecular networking analysis. Structurally diverse compounds including the polyketides 22-dehydroxymethyl-kijanolide (GH99 strain) and Abyssomicin I (GH176 strain) were detected in the extracts. Interestingly, Brevianamide F was detected in the extract of Micromonospora, which has previously been mostly found in fungal species. Other compounds such as cyclic tripeptides, Cyclo(l-Pro-d-Ile) and Cyclo(d-Pro-l-Phe), were also identified in this strain. In summary, for the first time, we explored the diversity of Actinobacteria and evaluated their bioactive potential from the Unkeshwar hot springs. The potent strains isolated in the study could be useful in drug discovery programs.